Hubungan Asupan Protein dan Status Gizi Dengan Tekanan Darah Penderita Hipertensi di Puskesmas Mengwi II - Dewi Kusumayanti, Gusti Ayu; Wiardani, Ni Komang; Permatasari, Novita (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
Hypertension is one of the serious health problems, it has even become a public health problem and will become a bigger problem if it is not addressed early. A person's blood pressure limit is said to be hypertension if the systolic pressure is more than 140 mmHg and the diastolic pressure is 90 mmHg. Patients with high blood pressure / hypertension are a disease that one of them must maintain daily intake, pay attention to nutritional status so as not to be obese and maintain ideal body weight. One of them must maintain protein intake, because it can affect blood flow in the blood vessels. More nutritional status or obesity can also affect the blood pressure of hypertensive patients. The purpose of the study was to determine the relationship between protein intake and nutritional status with blood pressure of hypertensive patients at Mengwi II Health Center. Observational research type with Cross Sectional design and using Consecutive Sampling technique which amounted to 34 people. Data were collected by interview and measurement methods. Data is presented with frequency tables and cross tables then variable data is tested for normality. The results of the Chi Square correlation analysis test showed that there was a relationship between protein intake and blood pressure of hypertensive patients (p = 0.039). While nutritional status with blood pressure of hypertensive patients, based on the results of the chi square test showed there was a relationship (p = 0.029).